Reduced Expression of VAMP8 in Lacrimal Gland Affected by Chronic Graft-versus-Host Disease. (30th September 2017) - Fukui, Masaki; Ogawa, Yoko; Mukai, Shin; Kamoi, Mizuka; Asato, Teru; Kawakami, Yutaka; Tsubota, Kazuo
Abstract : Purpose . To investigate whether the SNARE protein vesicle-associated membrane protein 8 (VAMP8) was implicated in the development of chronic ocular graft-versus-host disease (GVHD). Methods . Firstly, the chronic GVHD (cGVHD) and Sjögren's syndrome (SS)-impaired lacrimal gland (LG) tissue sections from humans for diagnostic purpose were evaluated for VAMP8 expression by histopathology and immunohistochemistry. Next, serial changes of tear secretion and VAMP8 expression at both protein and mRNA level of LG in an animal cGVHD model compared with the syngeneic control. Results . Decreased VAMP 8 expression in the cGVHD-affected human LG was detected in comparison with SS-affected LG. Tear secretion in the murine cGVHD model was significantly reduced compared with that in the syngeneic controls 8 weeks after BMT. Protein expression of VAMP8 in the cGVHD-affected LG in murine cGVHD was decreased in comparison with that in the controls. Gene expression of VAMP8 in the cGVHD-affected murine LG was significantly less than that in the syngeneic control 3 weeks after BMT. Conclusions . Our results suggested that expression of VAMP8 in the cGVHD-affected LG was decreased and accordingly tear secretion in cGVHD was reduced. Collectively, the reduction of VAMP8 expression in the cGVHD-affected LG can be involved in the pathogenic processes of cGVHD-induced dry eye disease.